Japanese university students’ perceived overweight and actual weight : relationship with a wish to die - Nadzirah Ahmad Basri,; Chen, Sanmei; Chen, Tao; Kumagai, Shuzo (Penerbit Universiti Kebangsaan Malaysia, 2017)
Previous studies demonstrated that perceived overweight has a larger role than actual body weight does in suicidal ideation and attempts. Despite high suicidal rate found among university students, studies have been limited in examining the role of perceived overweight in relation to suicidality in this population. This study aims to examine the relationship between a wish to die with perceived overweight and actual weight, measured by Body Mass Index (BMI) in university students. The sample comprised of 2,000 incoming freshmen in a Japanese university. Multivariate logistic regression was used to determine the association between a wish to die and perceived overweight and actual weight. Results indicated a wish to die prevalence of 5.8% (n=115) and perceived overweight prevalence of 15.8% (n=315) among the freshmen. Perceived overweight significantly increased the odds of a wish to die by two-fold (Odds Ratio (OR) =2.01, 95% Confidence Interval (CI) = 1.20- 3.37), in contrast to actual weight which was not significantly associated with a wish to die. Findings implied the necessity to promote healthy attitudes towards body weight and self-acceptance regardless of weight status among university students that could reduce the potential risk of a wish to die from progressing along the continuum of suicidality in later life.